MAIN TRENDS OF PRIMARY MALIGANT TUMORS AND PRIMARY DISABILITY OF THE ADULT POPULATION OF THE OMSK REGION IN 2007–2012 YEARS - S. P. Zapariy; V. K. Kosenok; A. K. Ivanilov (Сибирский онкологический журнал, 2016)
The analysis of primary cancer and primary disability of adult population of the Omsk region during the period 2007 to 2012 and medical-social characteristics has been presented.